Pilgrimage Rituals In Islam: An Anthropological Analysis of Practices, Meanings, and Social Changes - Budi Purwanto; Wawan Wahyuddin; Sholahuddin Al Ayubi (Dirasah International Journal of Islamic Studies, 2025)
This study examines Islamic pilgrimage rituals as dynamic socio-cultural practices within contemporary Muslim society, focusing on pilgrimage activities in Banten Lama, Serang, Banten, Indonesia, one of the major Islamic pilgrimage destinations in western Indonesia. Employing a qualitative ethnographic approach, the research investigates how pilgrimage rituals are constructed through the interaction of religious beliefs, local traditions, economic interests, and institutional authority. Fieldwork was conducted over three months using participant observation, in-depth interviews, and documentation involving five informants, including pilgrims, religious leaders, local traders, site managers, and community members. Data were collected through field notes, audio recordings, and visual documentation, and then analysed thematically to identify recurring socio-cultural patterns within pilgrimage practices. The findings reveal that pilgrimage rituals are contextual religious practices shaped by local culture, religious authority, and collective social experience. Pilgrimage sites function not only as sacred religious spaces but also as arenas of negotiation between theological discourse, popular religious expressions, and state regulation. Furthermore, pilgrimage activities contribute significantly to the socio-economic transformation of local communities through the expansion of religious tourism, trade networks, and service-oriented economic activities. The study also demonstrates that the commodification of pilgrimage does not necessarily diminish its sacred dimension; instead, it reflects an adaptive negotiation between spirituality and economic livelihood. Theoretically, this research contributes to the anthropology of religion by emphasizing pilgrimage as a lived religious experience shaped by symbolic interaction, cultural adaptation, and social negotiation in contemporary Muslim societies.